2017
DOI: 10.1038/oncsis.2016.84
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HOXA-AS2 represses P21 and KLF2 expression transcription by binding with EZH2, LSD1 in colorectal cancer

Abstract: Long noncoding RNAs (lncRNAs) have received increased attention as a new class of functional regulators involved in human carcinogenesis. HOXA cluster antisense RNA 2 (HOXA-AS2) is a 1048-bp lncRNA located between the HOXA3 and HOXA4 genes in the HOXA cluster that regulates gene expression at a transcription level. HOXA-AS2 is previously found to be overexpressed in gastric cancer (GC) and promotes GC cells proliferation. However, its potential role and molecular mechanism in colorectal cancer (CRC) are not kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 36 publications
(40 reference statements)
5
85
0
Order By: Relevance
“…Xie et al [23] showed that HOXA-AS2 epigenetically silences P21, PLK3, and DDIT3 in gastric cancer cells via binding to EZH2. Moreover, Ding et al [13] proved that HOXA-AS2 recruits EZH2 and LSD1 to the p21 and KLF12 promoter regions, which inhibits p21 and KLF12 translation. Accordingly, further investigations of whether other mechanisms are involved in HOXA-AS2-mediated miR-373 expression changes should be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al [23] showed that HOXA-AS2 epigenetically silences P21, PLK3, and DDIT3 in gastric cancer cells via binding to EZH2. Moreover, Ding et al [13] proved that HOXA-AS2 recruits EZH2 and LSD1 to the p21 and KLF12 promoter regions, which inhibits p21 and KLF12 translation. Accordingly, further investigations of whether other mechanisms are involved in HOXA-AS2-mediated miR-373 expression changes should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA HOXA cluster antisense RNA 2 (HOXA-AS2) was first reported to be an apoptosis suppressor in NB4 promyelocytic leukemia cells treated with all-trans retinoic acid [12]. Subsequent studies showed that HOXA-AS2 is aberrantly expressed in several human cancers and functions as an oncogene [13, 14]. However, little is known concerning its expression in glioma and its potential role in glioma malignancy and VM.…”
Section: Introductionmentioning
confidence: 99%
“…The results of clinical features showed that TUSC7 was associated with tumor size, HOTAIR with tumor size and TNM-stage. In table 1, we concluded a correlation with CRC clinical features and lncRNAs for visually understanding that lncRNAs might be as markers for CRC diagnosis (Table 1) [16, 17, 47, 57, 75-80]. Sun et al reported that ANRIL could enhance cell mobility and invasion by in-vitro tube formation HLECs invasion.…”
Section: Clinical Significance Of Lncrnas For Crcmentioning
confidence: 98%
“…The results of clinical features showed that H19 was associated with TNM-stage, tumour differentiation, HOTAIR with TNM-stage, tumour differentiation vessel invasion. Similarly, the FOXP4-AS1and HOXA-AS2 showed onco-role in promoting CRC proliferation and apoptosis [16, 17]. These evidences displayed unfavourable prognostic markers for CRC patients.…”
Section: Clinical Significance Of Lncrnas For Crcmentioning
confidence: 99%
See 1 more Smart Citation